Performance Index Model of Raw Water Infrastructure - Sri U. Sudiarti; Ussy Andawayanti; Lily M. Limantara; Hari Siswoyo (Salehan Institute of Higher Education, 2024)
This research intends to build a performance index model of raw water infrastructure mathematically by considering technical, non-technical, and environmental aspects. The research location is in Lombok and the Sumbawa Islands. Data is collected by field surveys and questionnaires that are distributed to 160 respondents related to raw water infrastructure in 21 locations. The methodology consists of Partial Least Squares (PLS) and Generalized Reduced Gradient (GRG). The results show that technical, non-technical, and environmental aspects have a significant influence on the performance index of raw water infrastructure. The structural analysis shows that the technical, non-technical, and environmental variables have a positive and significant influence on the performance index. The performance index of raw water infrastructure is successful enough to be developed and tested by using field data and GRG. The evaluation result shows that the model gives an accurate estimation of raw water infrastructure performance in Nusa Tenggara Barat province. The performance index model for raw water infrastructure is as follows: 0.521 IKTK + 0.305 IKNT + 0.174 IK Liwith the sum of square residual (SSR) is 83.21, the root mean square error (RMSE) is 0.44, the mean square error (MSE) is 3.97, and the accuracy level is 95.25%. This research provides the development of an evaluation method for raw water infrastructure performance and a valuable outlook for policymakers in managing and maintaining raw water infrastructure to support sustainable water resources in the future. Considering some aspects of this, it is hoped the efforts to increase the quality of raw water infrastructure can be more directed and effective, contributing to increasing society's prosperity and a sustainable environment in the region. Doi: 10.28991/CEJ-2024-010-06-014 Full Text: PDF